I am reading Acemoglu's intro to modern economic growth. But I am having trouble understanding his proof to a theorem related with stability. Here is the theorem: enter image description here

And here are some related definitions and theorems: enter image description here enter image description here

My question lies in his proof of corollary $2.1$. How did he show that the sequence $x(t)$ is monotone and bounded above by $x^*$? I think it is not enough to use that the derivative is less than $1$ and the distance to $x^*$ is shrinking to say $x(t)$ is monotone. Can someone give me some more details to understand the proof?


  • $\begingroup$ Given that $|a|<1$ and the linear difference is affine, ratio being less than 1 (dividing the RHS over to the left) is enough to get monotone. Try some examples. $\endgroup$
    – VCG
    Sep 16, 2016 at 1:49
  • $\begingroup$ It only says the distance is decreasing, and it does not eliminate the case say $x(0)=1, x^*=3, x(1)=4, x(2)=2.5, x(3)=3.25...$, or even an extreme case that $x^*=1, x(2k-1)=\frac{1}{2}- \frac{1}{2k-1}, x(2k)=\frac{3}{2}+\frac{1}{2k}$, where $x(t)$ does not converge to $x^*$ $\endgroup$
    – ask
    Sep 16, 2016 at 3:07
  • $\begingroup$ And also we are in the non-linear case... $\endgroup$
    – ask
    Sep 16, 2016 at 3:16

2 Answers 2


The OP correctly identified a mistake here. Since the author claims monotonicity for a general function, let's disprove it for the simple linear case. Consider

$$x_{t+1} = g(x_t) = -0.5x_t$$

This satisfies all the requirements and conditions stated by the author, and also that the derivative is smaller than unity in absolute values $\forall x$. But it converges with "damped oscillations", and so it is not monotonic since, say,

$$x_0 = -3 < 0 = x^*$$ $$x_1 = 1.5$$ $$x_2 = -0.75$$ etc

  • $\begingroup$ I believe you meant damped oscillations (reduced over time) rather than dumped $\endgroup$
    – Three Diag
    Oct 10, 2016 at 10:23
  • $\begingroup$ @ThreeDiag Thanks for spotting this. Fixed. $\endgroup$ Oct 10, 2016 at 23:14

Since the OP asked for a rigorous proof, here is one.

By Acemoglu's inequality in the first part of his proof, we can separate $\{x(t)\}_{t=0}^{\infty}$ into two subsequences, an increasing subsequence $\{x(t_{i})\}_{t_{i}\in I}$ bounded above by $x^{*}$ and a decreasing subsequence $\{x(t_{j})\}_{t_{j} \notin I}$ bounded below by $x^{*}$. Indeed, we define $I$ to be the set $\{t \in \mathbb{N} \mid x(t)<x^{*}\}$. By Acemoglu's inequality, $s>t$ implies $x(s)$ is strictly closer to $x^{*}$ than $x(t)$ is. Thus, since $x(t_{i})<x^{*}$ for all $t_{i} \in I$, $\{x(t_{i})\}_{t_{i}\in I}$ is increasing. Similarly, $\{x(t_{j})\}_{t_{j} \notin I}$ is decreasing and bounded below by $x^{*}$

Assume that each of these subsequences is infinite. Then each converges to a limit, which we will denote by $y$ and $z$ respectively.

Note that it also follows from Acemoglu's inequality that $y=x^{*}-\epsilon$ and $z=x^{*}+\epsilon$ for some $\epsilon \geq 0$. Indeed, suppose that this is not the case (we will show this generates a contradiction). For convenience, assume $\vert y -x^{*}\vert<\vert z-x^{*}\vert$. Define $$\delta:=\vert z-x^{*}\vert-\vert y-x^{*}\vert>0.$$ Since $\lim_{i \to \infty}x(t_{i})=y$, we can pick $t \in \mathbb{N}$ such that $$\vert x(t)-y\vert<\frac{\delta}{2}.$$ The triangle inequality then tells us that $$\vert x(t)-x^{*}\vert <\vert y-x^{*}\vert+\frac{\delta}{2}.$$ Now pick some $s \in \mathbb{N}$ such that $s >t$ and $x(s)>x^{*}$ (such an $s$ exists by our assumption that both the constructed subsequences are infinite). Since $x(s)>z>x^{*}$, we have that $$\vert x(s)-x^{*}\vert>\vert z-x^{*}\vert.$$ Thus, $$\vert x(t)-x^{*}\vert <\vert y-x^{*}\vert+\frac{\delta}{2}<\vert z-x^{*}\vert <\vert x(s)-x^{*}\vert.$$ But since $s>t$, this contradicts Acemoglu's inequality.

Now we will consider the value of $g(y)$. Since, $$g(y)=g(\lim_{i \to \infty}x(t_{i}))=\lim_{i \to \infty}g(x(t_{i}))=\lim_{i \to \infty}x(t_{i}+1),$$ we must have that $g(y)=y$ or $g(y)=z$.

If $g(y)=z$, then we must have that $y=z=x^{*}$ since if $y\neq x^{*}$, we get a contradiction. Indeed, if $y \neq x^{*}$, then Acemoglu's inequality implies that $g(y)$ is strictly closer to $x^{*}$ than $y$ is; but $y$ and $z$ are equidistant from $x^{*}$. Thus $g(y)=y$ and similarly $g(z)=z$. (If only one of the subsequences is infinite, we get this immediately.) But this implies that $y=z=x^{*}$, as Acemoglu's inequality allows us to infer that if $y \neq x^{*}$, then $g(y)$ is strictly closer to $x^{*}$ than $y$ is.

  • $\begingroup$ I'm not sure how you get to the claim that there are two monotone sequences whose limits are equally far from $x^\ast$. I think it would be good to be somwhat more specific where this comes from. $\endgroup$
    – tdm
    Sep 21, 2021 at 7:12
  • $\begingroup$ Thanks for the suggestion @tdm. I've updated the proof with more detail on that claim. $\endgroup$ Sep 21, 2021 at 9:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.